Policy Analysis of the Jabar Saber Hoaks Program in Addressing the Spread of Hoaxes in West Java - Hidayat, Hidayat; Wawan Gunawan; Dadan Kurnia; Zaenal Abidin AS (International Journal Administration, Business & Organization, 2026)
The rapid advancement of digital technology has become a vehicle for the spread of hoaxes, negatively impacting the lives of the digital community in Indonesia, particularly in West Java. On the other hand, public awareness regarding how to distinguish hoaxes remains low; this situation is further exacerbated by the emergence of AI technology, making it extremely difficult for the public to determine whether a piece of news is a hoax or not. To address the spread of hoaxes, the West Java Provincial Government issued a policy through West Java Governor’s Decree No. 700.05/Kep.1261-Diskominfo/2018 regarding the establishment of the Jabar Saber Hoaks program. This program aims to protect the public from the negative impacts caused by hoaxes. This study aims to analyze the policies of the Jabar Saber Hoaks program. Using a literature review approach, the findings indicate that the Jabar Saber Hoaks program’s policies have not been implemented optimally in protecting the public from the negative impacts of hoaxes. One reason for this is that Jabar Saber Hoaks only verifies information of questionable accuracy circulating in digital media, while community empowerment programs aimed at improving digital literacy have not been widely implemented. Consequently, many people in West Java have been affected by hoaxes, resulting in both moral and material losses.